Determinants of carotid intima-media thickness in patients with asymptomatic unstable plaques: a population-based cross-sectional study in rural China - Tang, Ping; Lu, Yuting; Xue, Huihui; Hao, Juan; Wen, Haotian; Tu, Jun; Chen, Ran; Li, Juan; Wang, Jinghua; Ning, Xianjia; Yang, Chunsheng; Li, Yan; et al. (Frontiers in Endocrinology, 2025)
PurposeStroke remains a leading cause of death and disability worldwide, with carotid intima-media thickness (IMT) and carotid plaque being significant predictors of cerebrovascular diseases. Despite the established correlation between carotid IMT and stroke, the specific factors influencing IMT in populations with unstable plaques are not well understood. This study aimed to identify the influential factors affecting carotid IMT in individuals with asymptomatic (without prior cardiocerebrovascular events) unstable plaques and to explore sex-specific differences.MethodsParticipants were recruited from 2713 patients who underwent carotid ultrasonography in Tianjin Jixian between 2019 and 2020. A total of 1070 individuals met the inclusion criteria, which required the presence of at least one unstable carotid plaque and no significant renal function abnormalities. Clinical and biochemical assessments were conducted, and carotid ultrasonography was performed to evaluate the IMT and plaque characteristics. Statistical analyses, including univariate and multiple linear regression analyses, were used to identify factors influencing IMT.ResultsThe study included 1070 patients with asymptomatic unstable plaques, comprising 616 males (57.6%) and 454 females (42.4%), with a mean age of 65.35 ± 7.75 years. Multivariate linear regression analysis confirmed that age (β = 0.247, P < 0.001), diabetes mellitus (β = 0.070, P = 0.046), and creatinine (β = 0.075, P = 0.036) were significant predictors of IMT in the overall population. In males, significant predictors included age (β = 0.209, P < 0.001), creatinine (β = 0.103, P = 0.010), and fasting plasma glucose (β = 0.086, P = 0.028). In females, significant predictors included age (β = 0.293, P < 0.001), diabetes mellitus (β = 0.113, P = 0.011), and smoking (β = 0.132, P = 0.003). These results emphasize the importance of considering sex-specific factors in the assessment and management of carotid atherosclerosis.ConclusionThese findings highlight the critical need for personalized approaches in reducing the risk of cerebrovascular diseases and improving patient outcomes. Among patients with asymptomatic unstable carotid plaques, male individuals need to focus more on renal function, while female requires more vigorous smoking cessation efforts.